Hospital Admission Patterns in Adult Patients with Community-Acquired Pneumonia Who Received Ceftriaxone and a Macrolide by Disease Severity across United States Hospitals - Thomas P. Lodise; Hoa Van Le; Kenneth LaPensee (Antibiotics, 2020)
(1) Objective: There are limited data regarding community-acquired pneumonia (CAP) admissions patterns in US hospitals. Current expert CAP guidelines advocate for outpatient treatment or an abbreviated hospital stay for CAP patients in pneumonia severity index (PSI) risk classes I–III (low risk); however, the extent of compliance with this recommendation is unclear. This study sought to estimate the proportion of admissions among CAP patients who received ceftriaxone and macrolide therapy, one of the most commonly prescribed guideline-concordant CAP regimens, by PSI risk class and Charlson comorbidity index (CCI) score. (2) Methods: A retrospective cross-sectional study of patients in the Vizient® (MedAssets, Irving, Texas) database between 2012 and 2015 was performed. Patients were included if they were aged ≥ 18 years, had a primary diagnosis for CAP, and received ceftriaxone and a macrolide on hospital day 1 or 2. Baseline demographics and admitting diagnoses were used to calculate the PSI score. Patients in the final study population were grouped into categories by their PSI risk class and CCI score. Hospital length of stay, 30-day mortality rates, and 30-day CAP-related readmissions were calculated across resulting PSI–CCI strata. (3) Results: Overall, 32,917 patients met the study criteria. Approximately 70% patients were in PSI risk classes I–III and length of stay ranged between 4.9 and 6.2 days, based on CCI score. The 30-day mortality rate was <0.5% and <1.4% in patients with PSI risk classes I and II, respectively. (4) Conclusions: Over two-thirds of hospitalized patients with CAP who received ceftriaxone and a macrolide were in PSI risk classes I–III. Although the findings should be interpreted with caution, they suggest that there is a potential opportunity to improve the efficiency of healthcare delivery for CAP patients by shifting inpatient care to the outpatient setting in appropriate patients.